Analysis and Design Information System using CPM (Critical Path Method) Method the web-based at PT.Pakarti Tirtoagung - Bella Liantono; Edy Edy (Tech-E, 2019)
Project planning has several stages or project activity plans that can result in the running of a project more optimally to the project estimation that can help the planning manager or project manager work together in preparing project implementation at PT. Pakarti Tirtoagung. PT. Pakarti Tirtoagung is a business that will produce an intangible product (service) / service activity for construction and oil services that will be used for the needs of other companies. Problems at PT. Pakarti Tirtoagung in processing project data using the MS system. Excel which results in data redundancy so it must check data - data and must be input again. This results in data redundancy and lack of data consistency so the presentation of project manager information is less accurate. Then this research uses CPM (Critical Path Method) method to determine the level of project progress in order to optimize project duration, possibility of accelerating time of project implementation and make it easier as admin by supporting project estimation activities, making it easier to manage planning of project activities and preparing a project scheduling. The design is implemented using PHP and MySQL database servers.